Drastic Effects on the Microbiome of a Young Rower Engaged in High-Endurance Exercise After a Month Usage of a Dietary Fiber Supplement - Jaago, Mariliis; Timmusk, Uku Siim; Timmusk, Tõnis; Palm, Kaia (Frontiers in Nutrition, 2021)
Food supplements are increasingly used worldwide. However, research on the efficacy of such supplements on athlete’s wellbeing and optimal sports performance is very limited. This study performed in junior academic rowing explores the effects of nutritional supplements to aid to the high energy requirements at periods of intense exercise. Herein, effects of prebiotic fibers on the intestinal microbiome composition of an 18-year athlete exercising at high loads during 8 months period in a “real-life” setting were examined using next generation sequencing analysis. Results demonstrated that although the alpha diversity of the subject’s microbiome drastically decreased (from 2.11 pre- competition to 1.67 (p <0.05)) upon fiber consumption, the Firmicutes/ Bacteroidetes ratio increased significantly (from 3.11 to 4.55 (p <0.05)). Underlying these macro‐level microbial alterations resulting were demonstrable shifts from acetate- to butyrate producing bacteria, although with stable effects on the Veillonella species. To our knowledge, this a unique study that shows pronounced changes in the gut microbiome of the young athlete at the competition season and their favorable compensation by the dietary fiber intake. The data here expand the overall understanding of how the high energy needs in high-intensity sports like academic rowing could be supported by dietary fiber supplement consumption.